(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
In Health, very often we need to judge if an exposure is a cause of a disease. In order to perform correct judgements, reasoning must obey to standardized criteria, being those published by Bradford Hill the most commonly used. Furthermore, research architecture must comply with different models, with different design characteristics and different levels of epidemiological proof. Another very important aspect is the recognition and minimization of errors and bias, some particular to each type of study and other general to the epidemiological research.